Предмет: Алгебра,
автор: annanesterenko812
6) 2/(a ^ 2 - 9) - 1/(a ^ 2 + 3a)
Ответы
Автор ответа:
0
Объяснение:
2/(а² - 9) - 1/(а² + 3а) = 2/(а-3)(а+3) - 1/а(а+3) =
2а - (а - 3) / а*(а - 3)(а + 3) =
2а - а + 3 / а(а - 3)(а + 3) =
а + 3 / а(а - 3)(а + 3) = 1/а(а - 3) = 1/(а² - 3a)
Похожие вопросы
Предмет: Биология,
автор: sidletskaalisa2412
Предмет: Українська мова,
автор: nikitjs1207
Предмет: География,
автор: lkuzmich870
Предмет: Физика,
автор: bakytzanulydidar
Предмет: Литература,
автор: mikosh008